Penyuluhan, Pemeriksaan Mata, Gula Darah Kolesterol Dan Asam Urat Pada Masyarakat Kecamatan Sukmajaya, Depok, Jawa Barat - Noviani Prasetyaningsih; Anggraeni Adiwardhani; Riani Witjaksana; Isa Bella; Jihan Samira; Ida Effendi; Monica Dwi Hartanti (CV. Multi Kreasi Media, 2023)
Dry eye disease is a disease with a fairly high prevalence worldwide. Old age and women are dominant risk factors for this disease. Other risk factors are systemic diseases such as Diabetes Mellitus and Hypercholesterolemia. External factors can also trigger the onset of this disease, such as ultraviolet rays, low humidity, wind, dust, and pollution, such as cigarette smoke, vehicle exhaust, or pollution from industry. In addition, excessive use of electronic devices such as mobile phones, computers, and laptops can cause the eyes to become tired quickly. Indonesia, which is a country with a lot of sunlight, pollution in big cities, and smoking habits, as well as the high number of DM and cholesterol patients, causes the prevalence of Dry Eye Disease in Indonesia to be quite high. The Community Service Program carried out by the Faculty of Medicine, Trisakti University, with the theme